IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MI 02 SIDOHARJO KECAMATAN PENAWARTAMA - Muhammad Agung; Erik Novianto; willy Radinal (UNISAN JURNAL, 2024)
As the manager of a school apart from being an educator, the principal is the top manager. Managing a school so that all of the school’s potential functions optimally is not an easy job. Maximum managerial expertise is required. Based on preliminary research, the objective condition is that teacher performance is still not optimal, due to: the lack of infrastructure, the lack of concern for the teacher board towards the rules and policies imposed by the school principal such as the policy of having picket teachers who monitor teacher attendance, it turns out that there are still unscrupulous teachers who do not for important reasons leaving effective study hours, there are still many teachers teaching without any preparation for teaching, many teachers are less motivated in teaching. This is where principal management is required to improve teacher performance. The focus of the research problem is Principal Management in Improving Teacher Performance MA Raudlatul Hidayah Maarif Nu 03 Contains Sari Lampung Timur. The research objectives were to identify and describe: 1) Implementation of the Principal’s Management function in improving teacher performance at MA Raudlatul Hidayah Maarif Nu 03 Contains Sari Lampung Timur; 2) Supporting factors and inhibiting factors for the Principal Management function in improving teacher performance at MA Raudlatul Hidayah Maarif Nu 03 Contains Sari Lampung Timur. This study used a qualitative approach, using interviews, observation and documentation. The results of the study: